itu Pendampingan Pengelolaan Sampah Organik dan Anorganik di Desa Mandala Kecamatan Rubaru : pendampingan pengelolaan sampah - Marisal Haq (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
One of the main factors causing environmental problems is pollution originating from waste. This happens because of low public awareness of the importance of good waste management. The waste management used by the community is by throwing it in the usual place to be burned so that the waste accumulates. The aim of this service is to assist in the management of inorganic waste into handicrafts and organic waste into fertilizer in Mandala Rubaru village. The method used to achieve this goal is to seek sufficient information about the waste problem, namely by conducting interviews with village officials to see in general the sources of waste generation, empowering village youth through the transfer of knowledge by visiting UPT Jatian and learning practices by children. around the post. Based on the results of the service, the majority of inorganic waste produced comes from schools. The waste will be used to make handicrafts. And most of the organic waste comes from people's homes, this organic waste is turned into compost. This is one of the waste management activities carried out by the community service team in Mandala Village.